Strategi Guru Kelas Dalam Meningkatkan Kedisiplinan Belajar Siswa di MA Palapa Nusantara - Ahmad Jalaluddin (Pendidikan Al-Gafari, 2024)
School is an institution that operates in the field of education which is one of the critical components for producing and creating citizens who have good attitudes, are responsible, disciplined, and useful for their nation and country, by what is expected from national education. This research aims to determine student discipline, the internal conditions of the school that influence it, and teacher strategies and solutions at MA Palapa Nusantara. The type of research used is descriptive qualitative research, data is obtained by observing, interviewing, and documenting. The validity of the researcher's data uses triangulation techniques. Data analysis was carried out in four stages: data collection, data reduction, data presentation, and conclusion. The results of the research show that the learning discipline students at MA Palapa Nusantara face several problems as follows: (1) students arrive late, (2) not complete assignments on time, (3) not pay attention to lessons, some students don't bring school equipment, and outside of class there are still students who don't make good use of their free time or breaks. Internal conditions that influence student learning discipline at MA Palapa Nusantara include (1) consistent school policies, (2) supportive school culture, (3) parental involvement, and (4) relationships between teachers and students. The teacher's strategy for improving students' learning discipline is by giving rewards, giving praise, giving punishment, advice, and teachers giving good examples to students.